The Phenomenon of Double Regulation and The Development of Prison Culture in The Interaction Between Street-Level Bureaucracy and A Semi Autonomous Social Field at Cipinang Prison and Batam Detention Center - Fitri, Adzra Salsabila; Olii, Mohammad Irvan (Jurnal Indonesia Sosial Sains, 2026)
This research examines the phenomenon of double regulation within correctional institutions—namely the coexistence and conflict between formal state rules and informal inmate norms—through a comparative analysis of Class I Cipinang Prison and Class IIA Batam Detention Center. The research is grounded in the evolving forms of pains of imprisonment in modern correctional systems, including procedural strain (tightness), impunity, and social stratification that shape prison culture. Using a descriptive qualitative approach, the study seeks to understand the social dynamics, bureaucratic practices, and power relations among actors inside prisons. The data were analyzed contextually to uncover the mechanisms through which dual systems of regulation emerge and affect prisoners' lived experiences and officers' conduct. Findings reveal that double regulation is shaped by complex social stratification (particularly in Cipinang Prison) and direct officer-inmate interactions that allow informal norms to fill gaps in formal regulations (notably in Batam Prison). Overcrowding intensifies officers' discretion, informal negotiations, and mutualistic consolidation between colleagues and staff, resulting in normative uncertainty, continuous psychological strain, and weakened rehabilitation and correctional programs. Nonetheless, prison culture also provides temporary operational stability through mechanisms of internal control. The study recommends structural reform, stronger accountability systems, institutional cultural transformation, harmonization of standard operating procedures, and further comparative research to reduce the adverse effects of double regulation and improve correctional governance in Indonesia.